Levosimendan in lung transplant recipients on VA‑ECMO - S. V. Zhuravel; V. E. Aleksandrova; I. I. Utkina; N. K. Kuznetsova; E. A. Tarabrin (Вестник трансплантологии и искусственных органов, 2020)
Chronic heart failure is one of the most dreadful complications in the early postoperative period following lung transplantation. At the same time, the effect of using levosimendan in the early post-lung transplant period is currently insignificant and remains debatable. This paper presents a clinical case where levosimendan was successfully used in a patient with right ventricular heart failure during lung transplantation undergoing central venoarterial extracorporeal membrane oxygenation (VA-ECMO).